Un panthéon martyrial censuré par Isabelle II : enquête sur l’estampe « Víctimas de la causa popular » - Pierre Géal (Cahiers de Civilisation Espagnole Contemporaine)
As early as 1820, the liberals developed a martyrdom pantheon that provided their movement with heroic referents capable of embodying the values they defended, but also of stimulating the political commitment of their compatriots. Particularly innovative, the lithograph « Víctimas de la causa popular », designed by Victoriano Ametller and Louis Charles Legrand, dated 1853, implements a graphic and textual discourse that is both complex and highly effective, which aims to bring together beyond of the Republican-Democratic camp. Its impact is confirmed by the reaction it provoked from Isabella II, who tried to censor it.